Carbon Dot‐Based Hydrogels: Preparations, Properties, and Applications. Issue 17 (29th January 2023) - Wang, Yijie; Lv, Tingjie; Yin, Keyang; Feng, Ning; Sun, Xiaofeng; Zhou, Jin; Li, Hongguang
Abstract: Hydrogels have extremely high moisture content, which makes it very soft and excellently biocompatible. They have become an important soft material and have a wide range of applications in various fields such as biomedicine, bionic smart material, and electrochemistry. Carbon dot (CD)‐based hydrogels are based on carbon dots (CDs) and auxiliary substances, forming a gel material with comprehensive properties of individual components. CDs embedding in hydrogels could not only solve their aggregation‐caused quenching (ACQ) effect, but also manipulate the properties of hydrogels and even bring some novel properties, achieving a win–win situation. In this review, the preparation methods, formation mechanism, and properties of CD‐based hydrogels, and their applications in biomedicine, sensing, adsorption, energy storage, and catalysis ‐are summarized. Finally, a brief discussion on future research directions of CD‐based hydrogels will be given. Abstract : The features of this review include i) preparations of CD‐based hydrogels, including CDs/polymers, CDs/low molecular weight gelators, CDs/graphene oxide, CDs/metal ions and derivatives of CD‐based hydrogels ii) properties of CD‐based hydrogels, such as fluorescence, mechanical strength enhancement, self‐healing, and stimulus response. iii) applications of CD‐based hydrogels in biomedicine, sensing, adsorption, energy storage, and catalysis.